Loss to follow-up in “test and treat era” and its predictors among HIV-positive adults receiving ART in Northwest Ethiopia: Institution-based cohort study - Bantie, Berihun; Seid, Awole; Kerebeh, Gashaw; Alebel, Animut; Dessie, Getenet (Frontiers in Public Health, 2022)
Background: People living with HIV/AIDS are enrolled in life-long Anti-Retroviral Treatment (ART) irrespective of their clinical staging as well as CD4 cell count. Though this "Universal Test and Treat" strategy of ART was found to have numerous benefits, loss from follow-up and poor retention remained a long-term challenge for the achievement of ART program targets. Hence, this study is aimed at addressing the much needed effect of the test and treat strategy on the incidence of loss to follow-up (LTFU) in Ethiopia. Method and materials: An institution-based follow-up study was conducted on 513 adults (age ≥15) who enrolled in ART at a public health institution in Bahirdar City, Northwest Ethiopia. Data were extracted from the charts of selected patients and exported to Stata 14.2 software for analysis. Basic socio-demographic, epidemiological and clinical characteristics were described. The Kaplan–Meier curve was used to estimate the loss to follow-up free (survival) probability of HIV-positive adults at 6, 12, 24 and 48 months of ART therapy. We fitted a multivariable Cox-model to determine the statistically significant predictors of LTFU. Result: - The incidence density of LTFU was 9.7 per 100 person years of observation (95% CI: 7.9–11.9 per 100 PYO). Overall, LTFU is higher in the rapid ART initiation (24% in rapid initiated Vs 11.3% in lately initiated, AHR 2.08, P-value=0.004), in males (23% males Vs 14.7% females, AHR1.96, P value=0.004), in singles (34% single Vs 11% married, with AHR1.83, P-value=0.044), in non-disclosed HIV-status (33% non-disclosed 11% disclosed, AHR 2.00 p-value =0.001). Patients with in poor/fair ART adherence were also identified as another risk groups of LTFU (37% in poor Vs 10.5% in good adherence group, AHR 4.35,P -value=0.001). Conclusion - The incidence of LTFU in this universal test and treat era was high, and the highest figure was observed in the first 6 months. Immediate initiation of ART in universal test and treat strategy shall be implemented cautiously to improve patient retention and due attention shall be given to those high-risk patients. Keywords- Loss to follow up , Predictors, Test and Treat strategy, Bahirdar city